The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/1010428317713394
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated expression of Cdc6 as BCR/ABL-dependent survival factor in chronic myeloid leukemia cells

Abstract: Chronic myeloid leukemia is characterized by the presence of the reciprocal translocation t(9;22) and the BCR/ABL oncogene. The BCR/ABL oncogene activates multiple signaling pathways and involves the dysregulation of oncogenes during the progression of chronic myeloid leukemia. The cell division cycle protein 6, an essential regulator of DNA replication, is elevated in some human cancer cells. However, the expression of cell division cycle protein 6 in chronic myeloid leukemia and the underlying regulatory mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The BCR-ABL1 kinase affects a wide range of intracellular signalling pathways ( 25 ) which might directly or indirectly modulate origin firing. The origin licensing factor Cdc6 is upregulated in a BCR-ABL1-dependent manner in primary CML and K562 cells ( 41 ), which may explain the increased activity of some origins. The DNA damage response (DDR) pathway is activated in CML ( 42 ), and DDR activation is known to repress late-firing origins.…”
Section: Discussionmentioning
confidence: 99%
“…The BCR-ABL1 kinase affects a wide range of intracellular signalling pathways ( 25 ) which might directly or indirectly modulate origin firing. The origin licensing factor Cdc6 is upregulated in a BCR-ABL1-dependent manner in primary CML and K562 cells ( 41 ), which may explain the increased activity of some origins. The DNA damage response (DDR) pathway is activated in CML ( 42 ), and DDR activation is known to repress late-firing origins.…”
Section: Discussionmentioning
confidence: 99%
“…Our GEP results demonstrated that genes encoding proteins involved in the S phase of cell cycle ( CCNA2 , CDK7 , CDC6 , DFB4 , MCM3 , and MCM6 ) were down-regulated after 12 months of nilotinib. Previous studies showed that these genes might promote the cell proliferation and DNA replication in CML CD34+/lin- cells at diagnosis [15, 36, 37].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, for the rst time we found that CDC6 expression was increased in DLBCL compared with reactive lymphocytic hyperplasia, CDC6 overexpression was often seen in non-GCB subtype and predicted adverse prognosis in patients with DLBCL. It has shown that CDC6 is overexpressed in several cancers such as lung (21), breast (8), ovarian (22) and prostate cancers (23) as well as chronic myelogenous leukemia (24). CDC6 overexpression can result from gene ampli cation, E2F1/2 upregulation (15,21) and alternative splicing, the latter of which predominantly generates a short CDC6 isoform resistant to degradation due to the loss of microRNA(miRNA)-binding sites in its 3'untranslated regions (25).…”
Section: Discussionmentioning
confidence: 99%